Prevalence and etiologies of macrosomia and low birth weight in 1000 neonates at Javaheri hospital in Tehran - Hematyar, M; Poormoslemi, A (Advances in Nursing & Midwifery, 2010)
Background and aim Low birth weight is one of the important problems in many societies especially developing ones. The survival rate of infants has a direct relationship with their birth weight. The aim of This cross-sectional study was to determine the prevalence and etiologies of Prevalence and etiologies of macrosomia and low birth weight in 1000 neonates of low birth weight (LBW) as well as macrosomia and their possible etiologies. Materials and methods 1000 neonates were sequentially selected by nonrandom sampling method over 6 months in 2006 at Javaheri hospital in Tehran. By reviewing their medical records, the birth weight of the subjects and other variables of the study were assessed. Independent T and Qui-square tests were used for data analysis. Findings In this study cross sectional- study mean weigh of the neonates was 2957±910 gr. 7% of the subjects suffered from low birth weight (mean=2371±260) and 3% had macrosomia (mean=4247±240). A significant relationship was found between birth weight and gestational age of the neonates. 10% of mothers having neonates with macrosomia had gestational diabetes. The etiology of macrosomia was not known in most cases. The most common causes of low birth weight included premature rupture of membranes, twin gestation, fetal distress and maternal conditions. Conclusion Appropriate gestational care, risk factor detection before pregnancy and improvement of quantity as well as quality of maternal child health services can reduce the number of low- birth-weight infants. Keywords: Macrosomia, Low birth weight, Prevalence, Etiology. *Corresponding Author: Dr. Masoomeh,<span style="font-size: 12pt; font-family: ";Times New Roman";; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: FA; mso-bidi-font-family: 'B Nazanin'; mso-ansi-language: EN-US;"> Hematyar. Islamic Azad University, College of Medicine, Tehran, Iran. E-mail: f_hemat@yahoo.com